Microbiological and physicochemical changes during ripening of Camembert cheeses made from raw or pasteurized cow's milk, produced in north of Algeria (Tizi Ouzou) - Hillal, Sebbane; Almi, Dalila; Hadouchi, Sonia; Hedjel, Louiza; Smail, Noria Saadoun; Mati, Abderrahmane (Indian Journal of Dairy Science, 2021)
This study was carried out on two types of Camembert produced in the region of Tizi-Ouzou (northern Algeria), one artisanal (AC) made from raw milk and the other industrial (IC) made from pasteurized milk. This work shows the effect of milk quality and cheese making processes on the evolution of physicochemical and microbiological parameters throughout a maturation period of 12 days. The result shows that the repining microflora and undesirable microbial populations were significantly higher (P < 0.05) in the raw milk than in the pasteurized. The physicochemical and microbiological parameters, during the ripening of the cheeses evolve in a similar way with significant differences according to the type and the stage of maturation. During the cheese repining period, AC showed more extensive (P < 0.05) lipolysis and proteolysis than IC. SDS-PAGE of water-soluble proteins (WSP) and insoluble fractions showed more extensive degradation of as-CN than Î²-CN.Â  The WSP profile, analyzed by Reversed-Phase High Performance Liquid Chromatography (RP-HPLC), was highest in AC than IC. The highest WSP profile was recorded at the 12th day of repining. The pathogenic flora decreased during the maturation process in AC. This development was confirmed by the results of the antibacterial effect of WSP, performed by the disc diffusion technique on E. coli and S. aureus strains. From this study it can be concluded that AC has a better organoleptic quality, safe for the Algerian consumer and more profitable for the Algerian cheese-breeders.